The Romance of the Romanoffs - McCabe, Joseph, 1867-1955 (Salt Lake City, UT : Project Gutenberg, 2018)
"The Romance of the Romanoffs" by Joseph McCabe is a historical account written in the early 20th century. The book delves into the history of the Romanov dynasty, presenting a critical narrative of the autocratic rule in Russia and its sociopolitical ramifications. It aims to illuminate the tragic and romantic elements of Russian history, particularly focusing on how the autocracy emerged and its impact on the Russian populace. The opening of the book sets the stage for a detailed exploration of Russia's history, emphasizing its early democracy among the Slavs and the subsequent descent into autocracy. McCabe reflects on the Russian character, suggesting that despite prevailing theories of the Slavs' indifference to democratic ideals, there has been a persistent struggle for freedom against oppressive rulers. He introduces the concept of the Romance of the Romanoffs as a tale of tragedy, brutality, and corruption, suggesting that the narrative will explore both the shortcomings of autocracy and the resilient spirit of the Russian people. (This is an automatically generated summary.)
The primitive democracy of the Slav -- The descent to autocracy -- The Moscovites become Tsars -- The rise of the Romanoffs -- The early Romanoffs -- A Romanoff princess -- The great Peter -- Catherine the Little -- Romance upon romance -- The gay and pious Elizabeth -- Catherine the Great -- In the days of Napoleon -- The fight against liberalism -- The tragedy of Alexander II -- Enter Pobiedonostseff -- The last of the Romanoffs.
Release date is 2018-02-20
Produced by David Thomas
Keywords: Romanov, House of; Russia -- Kings and rulers